Leftover Food as a Sustainable Source of Astaxanthin Through Fermentation Using Phaffia rhodozyma - Rossella Vadalà; Eleonora Di Salvo; Laura De Maria; Giovanna Lo Vecchio; Giovanni Bartolomeo; Rita De Pasquale; Claudia Genovese; Nicola Cicero; Rosaria Costa (Foods)
Natural astaxanthin is a bioactive with high antioxidant power, widely suitable for many applications. This study explores the potential of leftover food as a sustainable and low-cost substrate for producing astaxanthin via direct fermentation using Phaffia rhodozyma. The pretreated and characterized raw materials were fermented in a lab-scale bioreactor under optimized process conditions. The entire process (168 h) was monitored in terms of reducing sugar consumption, yield, and productivity of astaxanthin. The implemented experimental plan achieved high astaxanthin yield and producticity, namely, 230 mg·L−1 and ~1.6 mg·L−1·h, which were attained at 150 h, respectively, with a substrate consumption of around 90% for all samples. The natural astaxanthin obtained showed interesting antioxidant activity, exhibiting a radical scavenging activity of more than 65%, which was evaluated with a DPPH assay. This process not only offers a promising solution for leftover food valorization but also provides a sustainable approach to producing bioactive compounds with significant health value, paving the way for further industrial applications in food, pharmaceutical, and cosmetic sectors.